Winter sports special issue - Allen, T.; Sandbakk, O.; Lindinger, S. (Sports Engineering, 2017)
In all winter sports, equipment is essential for athlete performance and safety. Research into Sports Engineering , therefore, has a direct and tangible impact on the performance and safety of winter sports athletes. Prior to Sochi 2014, Sports Engineering published its first special issue on winter sports in Volume 16 Issue 4. Building on this success, Sports Engineering have dedicated this issue to winter sports, prior to PyeongChang 2018.